Analisis Pengaruh Desain Antarmuka Terhadap Keamanan Data Pengguna Pada Sistem Digital - Sahdaini, Risya; Zharah Paramitha; Tengku Nidaul Husna; Elvira Ramadhani; M. Khalil Gibran (Pusat Riset dan Inovasi Nasional, 2026)
The development of digital technology has increased the use of web-based and mobile systems, but it has also posed challenges related to the security of user data. This study aims to analyze the influence of user interface design on data protection in digital systems. The method used is a descriptive quantitative approach by collecting data through a Likert scale-based questionnaire to 20–30 respondents who actively use digital services. The data is analyzed to see the tendency of user perception of the relationship between interface design and data security. The results show that the majority of respondents agree and strongly agree that a clear, structured, and easy-to-understand interface design can improve understanding of security features and a sense of security in using digital systems. In addition, poor or confusing design has the potential to cause users to ignore the security aspect. These findings suggest that interface design has an important role not only in terms of convenience, but also in supporting the protection of user data. Therefore, the development of digital systems needs to integrate security aspects in interface design to increase user trust and vigilance.